Sandstone-Hosted Uranium Deposits as a Possible Source for Critical Elements: The Eureka Mine Case, Castell-Estaó, Catalonia - Montgarri Castillo-Oliver (Minerals, 2019)
The Eureka deposit in Castell-estaó in the Catalan Pyrenees is a Cu−U−V deposit, hosted by Triassic red-bed sandstones, and classified here as a low-temperature, sandstone-hosted stratabound metamorphite U deposit. The main mineralisation is stratabound, related to coal-bearing units and produced during the Alpine deformation by migration of hydrothermal fluids. In this stage, the original sedimentary and diagenetic components (quartz and calcite, micas, hematite and locally apatite) were replaced by a complex sequence of roscoelite, fine-grained REE phosphates, sulphides and Ni−Co arsenides and sulpharsenides, Ag−Pb selenides, bismuth phases, sulphosalts and uraninite. The black shales of the Silurian sediments underlying the deposit and the nearby Carboniferous volcanoclastic rocks are interpreted as the source of the redox-sensitive elements concentrated in Eureka. The sulphur source is related to leaching of the evaporitic Keuper facies. The REE transport would be facilitated by SO4-rich solutions. The reduction of these solutions by interaction with organic matter resulted in the widespread precipitation of REE and redox-sensitive elements, including many critical metals (V, Bi, Sb, Co), whereas barite precipitated in the oxidized domains. The occurrence of similar enrichments in critical elements can be expected in other similar large uranium deposits, which could be a source of these elements as by-products.